The Role of Technology in Supporting Differentiated Learning for Students with Diverse Learning Needs: A Systematic Literature Review - Sumarni, Sri Sumarni; Krisna Andhita; Adi Puta Yusti; Faris Nasrudin Ulwan; Yemima Purnama Sari; Rizka Aziz Wahab (Jurnal Inspirasi Pendidikan, 2025)
Differentiated learning is a strategic approach to meet the diverse needs, interests, and learning abilities of students. However, its implementation still faces various challenges. This study regularly examines the use of technology in supporting differentiated learning and analyzes the barriers to its implementation. The method used is a Systematic Literature Review of 15 articles indexed by SINTA, Scopus, or Semantic Scholar in the last five years, through the stages of identification, selection, quality assessment, and descriptive-analytical data synthesis. The results of the study show that the integration of technology, such as digital media, LMS, WebQuest, animated videos, and DVGs, is effective in facilitating the diverse learning needs of students. Technology supports teachers in designing adaptive learning, increasing motivation and learning outcomes, and facilitating the assessment and feedback process. However, challenges in the form of limited infrastructure, digital literacy, and teacher readiness are still major obstacles. Therefore, continuous training and strengthening of supporting facilities are needed so that the implementation of technology-based differentiated learning can run optimally and effectively. The study recommends the development of a more adaptive technology integration model.